Atrial fibrillation in patients with idiopathic hypertrophic subaortic stenosis. Issue 5 (September 1970) - Glancy, D. Luke; O'Brien, Kevin P.; Gold, Herman K.; Epstein, Stephen E.
Abstract : Atrial fibrillation occurred in 16 ( 10% ) of 167 patients with idiopathic hypertrophic subaortic stenosis. The clinical and haemodynamic findings in these 16 patients are presented . Atrial fibrillation appeared late in the course of the disease, and its occurrence did not seem to be related to the severity of left ventricular outflow obstruction or to the amount of associated mitral regurgitation. In each patient the onset of the arrhythmia was accompanied by severe clinical deterioration, which often necessitated urgent medical treatment. Digitalis was administered to all 16 patients with subsequent clinical improvement in 15. Electrical cardioversion was uniformly successful in restoring sinus rhythm, but atrial fibrillation usually recurred. In each of 8 patients catheterized during atrial fibrillation, cardiac output was strikingly low ( average, 1.9 l./min./m. 2 ), whereas it was normal in 10 of 13 patients studied in sinus rhythm. The duration of follow-up from the onset of atrial fibrillation has averaged 5 years, and 3 of the 16 patients have died of causes related to their heart disease. Four have suffered cerebral emboli. Only 5 patients are now in stable sinus rhythm; in general, they are less symptomatic than the patients in whom atrial fibrillation has recurred . The unusually severe clinical deterioration at the onset of atrial fibrillation and the low cardiac output measured during catheterization are thought to be related to the loss of the important contribution to ventricular filling of atrial systole in patients with poorly compliant ventricles, and to the effect of an irregular ventricular rhythm on the variable nature of the outflow obstruction.